Juvenile Hormone Effect on the Venom Gland Secretory Cycle in Workers of Apis mellifera (Hymenoptera, Apidae) - Roat, T. C. [UNESP]; Nocelli, R. C. F. [UNESP]; Silva de Moraes, R. L. M. [UNESP]; Cruz-Landim, C. [UNESP] (My University, 2004)
The present investigation analyzed the influence of Juvenile Hormone (JH) on the venom glands of Apis mellifera workers through protein dosage and electrophoresis of venom gland extracts of newly emerged workers which were treated with 1 μl JH dissolved in hexane, in concentration of 2μg/μl. Newly emerged workers non-treated and treated with 1 μl hexane were the controls. Both JH and hexane provoke quantitative changes on the gland protein titre and on the protein electrophoretic profile. The disappearance of protein bands in the venom gland extracts of 14 day-old treated workers, a situation normally found only in 35 day-old non-treated workers, suggests that the JH treatment induces a precocious maturation of the worker venom gland.
Keywords: Apis mellifera; Electrophoresis; Juvenile hormone; Proteins; Venom gland; Apidae; Apis; Hymenoptera